Effectiveness of Erikson's Ego Counseling as an Individual Counseling Approach - Bakhrudin All Habsy; Giralda Aufadzatul Hanan Akhmad; Neha Eka Meifiana; Widya Anggraeni; Nihayatul Latifia (Suluh: Jurnal Bimbingan dan Konseling, 2024)
Erikson's ego counseling is an individual counseling approach based on Erikson's theory of psychosocial development. This approach views that individuals develop through eight stages of ego development. The goal of Erikson's ego counseling is to help clients achieve ego integrity by overcoming psychosocial crises at each stage of development. This research aims to analyze the effectiveness of Erikson's ego counseling as an individual counseling approach through a literature review. The method used is a systematic literature review of previous research on the application and effectiveness of Erikson's ego counseling. The results of the study show that Erikson's ego counseling is effective in helping clients overcome problems in achieving developmental tasks, identity crises, career stagnation, and other psychosocial problems. Erikson's ego counseling has also been proven to be able to increase the achievement of ego integrity. In conclusion, Erikson's ego counseling is an effective individual counseling approach based on the literature review conducted.